Synthesis of 1, 8-naphthalimide-based probes with fluorescent switch triggered by flufenamic acid. Issue 6 (20th June 2018) - Saito, G.; Velluto, D.; Resmini, M.
Abstract : In this work, we report the synthesis of novel fluorescent molecules, based on 1, 8-naphthalimide thio- and amino-derivatives, designed to display an OFF-ON and ON-OFF photoelectron transfer fluorescence switch upon interaction with a proton-donor drug. We have functionalized the new probes to allow easy formation of a covalent link to polymer matrices, for future applications as drug delivery sensors. We have investigated the fluorescent switch of the new probes using flufenamic acid (FA, pKa 3.65), a water insoluble, non-steroidal anti-inflammatory drug, as a model drug and proton source. The rapid interaction of the new probes with FA resulted in fluorescence enhancement or decrease and a large Stokes shift, all of which allowed the detection of the drug in the nanomolar range. The new 1, 8-naphthalimide fluorescent dyes reported in this work are interesting tools for the detection and quantification of acidic drugs and biomolecules.